2012
DOI: 10.1017/edp.2012.3
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Adolescent Boys’ and Teachers’ Perceptions of the Student–Teacher Relationship

Abstract: Relationships between teachers and students vary and the way these relationships are perceived by their members also differs. Seventy Australian adolescent boys described their relationship with a key teacher using the My English Class questionnaire. The teachers described the same relationships using the Teacher Student Relationship Inventory. Student-teacher relationships generally were seen positively. Cluster analysis identified two distinct profiles of student-teacher relationship for both student and tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The handful of studies ( Gest et al, 2005 ; Hughes et al, 1999 ; Rey et al, 2007 ) that explored teacher-student relationships from the young people’s as well as teachers’ perspective around age 10 (from age 8 to 11), reported correlations of .16 to .25 between the two informants. One study ( Kavenagh et al, 2012 ) found that adolescent boys (mean age 13.10) and their teachers viewed their relationship generally positively; however, with relatively low concordance (44% were mismatched). Furthermore, while boys saw caring and helpful attitudes toward them alongside positive feedback as key to positive relationships with their teachers, teachers viewed youths’ help-seeking as key for defining the quality of their relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The handful of studies ( Gest et al, 2005 ; Hughes et al, 1999 ; Rey et al, 2007 ) that explored teacher-student relationships from the young people’s as well as teachers’ perspective around age 10 (from age 8 to 11), reported correlations of .16 to .25 between the two informants. One study ( Kavenagh et al, 2012 ) found that adolescent boys (mean age 13.10) and their teachers viewed their relationship generally positively; however, with relatively low concordance (44% were mismatched). Furthermore, while boys saw caring and helpful attitudes toward them alongside positive feedback as key to positive relationships with their teachers, teachers viewed youths’ help-seeking as key for defining the quality of their relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This is the only scale that was originally developed in an Asian context to measure the teacher-student relationship. The TSRI has dimensions such as satisfaction, instrumental help, and conflict, and has been used in Singapore (Ang and Raine, 2009;Chong et al, 2010;Huan et al, 2012), Australia (Kavenagh et al, 2012), and the United States (Suldo et al, 2014).…”
Section: Measurement Of Teacher-student Relationshipsmentioning
confidence: 99%